Information Access of Health in Transitional Societies - Abdi Mubarak Syam (Universitas Islam Negeri Sumatera Utara, Medan, 2022)
Hallucinations are sensory perception disorders that occur when a person's awareness is strong or full and occur in the absence of external stimuli. Those who have hallucinations frequently believe that the environment around them is the source or cause of their symptoms. Objectives: The goal of this study is to determine how family knowledge and attitudes about patient care with hallucinations in Prof. Dr. Muhammad Ildrem Mental Hospital Medan in 2022. Method: In research design, cross-sectional methodology and analytic research are used. A total of 98 respondents were drawn at random from the study's population, which included the patient's family. To collect data, the questionnaire is distributed. In data analysis, statistical tests for Spearman rank are used. Result: The findings of the study show a significant relationship between knowledge and attitudes toward hallucinations and family involvement in their care. This study employs an analytic descriptive method with a cross-sectional design, 98 respondents as samples, accidental sampling sampling strategies, and a population of 8,893 respondents. According to the study's findings, there was a relationship between family participation and hallucinating patients with a value of 0.38 (0.05) and a relationship between family attitudes and family participation with a value of 0.19 (0.05) with a confidence level of 95%. Respondents are expected to increase and strengthen their influence on the subject of hallucinations by providing any support to the subject, including assessment, instrumental, information, and emotional support.